Extension of the CityGML Schema for a New Model of Accessible Urban Environment - F. Di Stefano; E. S. Malinverni (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
The study explores the extension of the CityGML schema to improve accessibility analysis in urban environments. Given the increasing focus on making cities more inclusive, particularly historical centres, managing urban accessibility requires a multidisciplinary approach integrating cartographic and architectural data. The methodology involves data collection by geomatic sensors to realize 3D urban models using CityGML, incorporating semantic, geometric, and topological information to assess accessibility barriers. Through the Application Domain Extension mechanism, a new "UrbanAccessibility" class is introduced, enabling detailed mapping of urban obstacles and facilitating the design of inclusive pathways. The process involves with data management by means mobile mapping system, followed by 3D modeling and semantic structuring in a GIS geodatabase. The resulting model allows for real-time analysis, supporting accessibility plans such as the PEBA (Barrier-Free Environmental Planning) and PAU (Plan for Urban Accessibility Plan). The integration of accessibility attributes by CityGML enhances decision-making tools for urban planners and policymakers, promoting sustainable and inclusive urban development. Furthermore, the approach not only ensures continuous monitoring and updating of accessibility data but also advances urban planning towards a more equitable and barrier-free environment.